Digital transformation in managing outgoing student applications: Enhancing administrative efficiency in higher education institutions - Santos, E.; Trigo, A. (International Journal of Business Process Integration and Management, 2025)
Digital transformation is essential for improving the operational processes of organisations and, consequently, their performance. This work presents the prototype of a computer application to support the management of outgoing students' applications in a higher education institution. The key outcomes of this work include the systematisation of the process, the establishment of key performance indicators, and the real-time monitoring and traceability of students' applications. From a managerial perspective, this work provides insights for higher education institutions aiming to digitalise and control their processes. Moreover, it offers a practical framework that can be adapted by any industry seeking to implement controlled processes, enabling the collection of data from activities to feed the key performance indicators.